(3GdcTa Yf eLGhRI gPg GdCeI GdCdas - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3hHYO abO cKQ GdSDGd Yf GdMOjK GdeTJgQ Ydi CdSfI GdfGS Cf GdfHi dGjecK ai bHQg Cda SfI gd gh UMjM s
(3BNQgG (B:s
(3abGdJ WGFaI HCf GdGSe gh GdeSei hbGdJ WGFaI HCf GdGSe ZjQ GdeSei s
(3GdfSNI ChdgG eWehSs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1491s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs